Evaluation of intubating conditions after rocuronium bromide in adults induced with propofol or thiopentone sodium - Moazzam Md Shahnawaz; Bano Shahjahan; Siddiqui Suhail Sarwar (Wolters Kluwer Medknow Publications, 2011)
Aim: The aims of present study were to compare the propofol and rocuronium with thiopentone and rocuronium in terms of clinically satisfactory intubating conditions and to co-relate intubating conditions with degree of paralysis in adductor pollicis muscle using train of four ratio (TOFR). The intubating conditions were evaluated after rocuronium bromide 0.6 mg kg−1 at 60 s. Materials and Methods : 60 patients of ASA grades I-II of either sex, age 18-50 years, undergoing various elective surgical procedures were randomly divided into two groups, propofol rocuronium (PR group) and thiopentone rocuronium (TR group) of 30 patients in each. In the PR group, patients received propofol 2.5 mg kg−1 and rocuronium 0.6 mg kg−1 ; in TR group, patients received thiopentone 5 mg kg−1 and rocuronium 0.6 mg kg−1 . In all patients the intubating conditions were evaluated by the observer at 60 s. TOFR was measured at the time of intubation by an assistant. Results : In the PR group the number of the patients placed in intubating conditions grades I, II, III and IV were 40%, 36.67%, 13.33% and 10% and their mean TOFR were 31.8±17.9%, 61.8±;14.6%, 61.7±27.9%, and 78.3±5.7% respectively. While in theTR group the number of patients placed in intubating condition grade I, II, and III were 60%, 26.67%, and 13.33% and their mean TOFR , 41.2±28.3%, 68.0±10.9% and 78.7±6.8%, respectively. There was no patient in grade lV in theTR group. Conclusion : The clinical intubating conditions and degree of paralysis of adductor pollicis muscle after rocuronium 0.6 mg kg−1 at 60 s in adults induced with propofol or thiopentone sodium are comparable.